OUTCOMES OF INTRAOPERATIVE RADIOTHERAPY (IORT) FOR SPINAL TUMOURS - Ali, Sheikh Muhammad Ebad; Abbasi, Ahmed Nadeem; Zahoor, Naila (Journal of Ayub Medical College Abbottabad, 2022)
Background: The spinal column is a major site of neoplastic proliferation where decisions regarding surgical or radiotherapeutic intervention are based upon spinal instability neoplastic score (SINS). A novel technique named '˜Intraoperative radiotherapy (IORT) was proposed where surgery and radiotherapy were performed in the same session. During our literature search, we found no published systematic review or meta-analysis regarding the outcomes of IORT for spinal tumors. This review aims to provide the knowledge regarding the outcomes of IORT for spinal tumors to assist surgeons and radiologists. Methods: PubMed, Google Scholar, Cochrane library for trials reporting the outcomes of IORTin spinal tumors. The search terms were outcomes, Intraoperative radiotherapy, IORT, spine neoplasia and spine metastasis in different combinations. Standardized mean difference (SMD) in VAS for pain relief while proportionality for neurological improvement, local progression, and toxicities were plotted on forest plots, respectively. Results: Eight studies comprising 610 patients were included with two conference proceedings. SMD for VAS was -1.715 while proportionality for neurological improvement, local progression, and toxicities were 0.9 (90%), 0.03 (3%), and 0.121 (12.1%), respectively. Conclusion: Pain relief was evident by a decrease in VAS scores in the majority of patients. The majority showed neurological improvement and regained motor and sensory functions while an overwhelming population showed local tumor control with lesser patients developing tumor progression and radiation-induced toxicities. Short follow-ups and the absence of randomized trials advocates the need for further clinical researches to confirm the outcomes of IORT in spinal tumors.